Pendidikan Olahraga untuk Meningkatkan Prestasi Akademik Siswa: Kajian Interdisipliner - Hamzah, Alimin (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Physical education plays a crucial role in shaping students’ cognitive, social, and emotional abilities. This study aims to analyze the relationship between physical education and students’ academic achievement through an interdisciplinary approach. Using the Systematic Literature Review (SLR) method, this research follows the guidelines of Kitchenham & Charters (2007) and the PRISMA 2020 protocol. Twenty national and international journal articles published between 2020 and 2025 were thematically analyzed to identify patterns linking physical activity, cognitive function, learning motivation, and academic outcomes. The findings reveal that physical education positively influences academic achievement through three key mechanisms: enhancing cognitive functions through physical activity, strengthening motivation and self-regulation, and applying interdisciplinary learning approaches that integrate physical and academic aspects. The review also indicates that physical education fosters social values and character development that support students’ academic success. Therefore, physical education should not be viewed merely as a physical activity but as a holistic learning medium that reinforces kinesthetic, cognitive, and emotional intelligence. The results of this study are expected to serve as a reference for curriculum development and educational policy focusing on the integration of physical fitness and academic excellence.